Combining AMMI and Mean Yield of Wheat Genotypes Evaluated under Rainfed Conditions of Northern Hills Zone for Stability Analysis - Verma, Ajay; Singh, G. P. (International Journal of Bio-resource and Stress Management, 2021)
Highly significant effects of environment (E), GxE interaction and genotypes (G) observed by AMMI analysis during 2018-19 and 2019-20 study years. WAASB measure ranked suitability of UP 3039, VL 2035 and VL 2036 genotypes. Superiority index while weighting 0.65 and 0.35 for yield and stability found VL 2036, HS 668 and UP 3039 as of stable performance with high yield. PRVG and MHPRVG measures observed suitability of HS 668, HS 562 and HS 669 wheat genotypes. More over the average yield of genotypes ranked HS 668, VL 2036 and HS 669 as of order of choice. Mostly indirect relations of SI measure were observed with stability measures along with positive values for MHPRVG, PRVG and yield. WAASB measure exhibited significant indirect relationships with other measures except of moderate positive with SI, yield, MHPRVG and PRVG measures. For the second year of study WAASB measure ranked suitability of HS676, UP3064 and HS677 genotypes. Superiority index while weighting 0.65 and 0.35 for yield and stability found VL2041, HS675 and HS562 as of stable performance with high yield. PRVG and MHPRVG measures observed suitability of VL2041, HS675 and HPW470 wheat genotypes. More over the average yield of genotypes ranked VL2041, HS675 and HS507 as of order of choice. Mostly negative values were exhibited by SI measure with stability measures apart of direct with MHPRVG, PRVG and yield. WAASB measure exhibited direct relationships with other stability measures except of indirect relations with SI, yield, MHPRVG and PRVG.